1998
DOI: 10.1002/(sici)1521-3803(199810)42:05<317::aid-food317>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dried tomato, grape and apple pomace on the cholesterol metabolism and antioxidative enzymatic system in rats with hypercholesterolemia

Abstract: The effect of dried tomato, grape and apple pomace (5% in diet) on the cholesterol levels in serum and selected organs was studied in male Wistar rats fed a cholesterol diet (0.3%) shortly after weaning. Pomace of individual fruits contained 47.2, 67.0 and 46.2 g of total dietary fiber per 100 g of dry matter for tomato, grape and apple pomace, respectively. Corresponding values for the soluble components of the fiber were 10.3, 14.7 and 26.0%. None of the tested products affected the serum cholesterol levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
(21 reference statements)
2
19
0
Order By: Relevance
“…So, it cannot be said overall that grapes and derived products present positive effects on plasma cholesterol in animal studies. However, one of these studies (26) did find a reduction in cardiac cholesterol and in the half-times of serum [ 14 C]cholesterol decay curves, while another reported a decrease in aorta total cholesterol (63) .…”
Section: Total Cholesterol Ldl-cholesterol and Hdl-cholesterolsupporting
confidence: 82%
See 3 more Smart Citations
“…So, it cannot be said overall that grapes and derived products present positive effects on plasma cholesterol in animal studies. However, one of these studies (26) did find a reduction in cardiac cholesterol and in the half-times of serum [ 14 C]cholesterol decay curves, while another reported a decrease in aorta total cholesterol (63) .…”
Section: Total Cholesterol Ldl-cholesterol and Hdl-cholesterolsupporting
confidence: 82%
“…The same happened after supplementation to hamsters with different extracts from grapes (52) or to rats with grape pomace. In this last case, there was actually a significant loss of antioxidant capacity in the liver (26) . These differences in results of similar assays may be related to the various limitations that have been reported in the determination of plasma antioxidant capacity (97) , as well as to differences in the designs of the studies (duration of treatment, doses employed).…”
Section: Plasma Antioxidant Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…This result is in accordance with Aprikian et al (2002), who found that when cholesterol-fed rats were supplemented with apples, there was a significant drop in plasma cholesterol and an increase in high-density lipoproteins (HDL). More studies investigated these parameters using apples, pears and peaches, with apples having the greatest effect (BOBEK; OZDÍN; HROMADOVÁ, 1998;LEONTOWICZ et al, 2003). Apples contained more phenolic compounds, suggesting that perhaps the phenolics in apples contribute to this effect ( LEONTOWICZ et al, 2002).…”
Section: Hdl-cmentioning
confidence: 99%